Patient-doctor concordance of perceived mental health service needs in Chinese hospitalized patients: a cross-sectional study - Yu, Jian-Ying; Dong, Zai-Quan; Liu, Yang; Liu, Zi-Han; Chen, Liang; Wang, Jian; Huang, Ming-Jin; Mo, Li-Ling; Luo, Shan-Xia; Wang, Yu; Guo, Wan-Jun; He, Ning; et al. (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Background: To assess the subjective concordance on mental health service needs in hospitalized patients between patients and doctors in China. Methods: A cross-sectional study was performed in one day. All hospitalized inpatients from selected departments of West China Hospital were recruited as potential participants. A questionnaire set including demographic variables and the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder 7-item scale (GAD-7) questionnaires were completed by the included patients. They and their doctors in-charge were asked if they perceived that the patients needed mental health services. Results: The overall response rate in patients was 84.25% and the final sample consisted of 1,273 patients. Among those, 605 patients (47.53%) themselves believed that they needed mental health services, whereas only 345 patients (27.10%) were deemed to be in need of mental health services only by their doctors. Kappa statistics showed that the concordance rate between patients and doctors was low in the total patient group (kappa =0.055) and in the group of patients with significant depression or anxiety (kappa =0.080). A logistic regression analysis showed that the ward where the patients were treated was related to a consistent recognition of mental health needs (OR =1.667). Conclusions: The concordance between Chinese inpatient perception and doctor evaluation of mental health service needs for these patients was low. Therefore, it seems necessary to develop effective strategies to improve the detection rate, such as the use of screening-instruments and the training of health professionals in the detection of psycho-social distress.